Surveillance of phlebotomine fauna and Didelphis marsupialis (Didelphimorphia: Didelphidae) infection in an area highly endemic for visceral leishmaniasis in Colombia (2019)
ABSTRACT: Introduction: The study of the interaction between the parasite, the vector and the mammalian hosts, including man, allows to understand the behavior of the leishmaniases. Objective: To determine the presence of Lutzomyia species and to detect the Leishmania infection in Didelphis marsupialis in an endemic area for visceral leishmaniasis. Materials and methods: Phlebotomine fauna and individuals of D. marsupialis were collected with CDC and TomahawkTM traps, respectively. The species of Lutzomyia were identified using the Young and Duncan key (1994). Ear and tail biopsies and blood samples from D. marsupialis were taken to identify the Leishmania species by amplifying a fragment of the gene associated with the 70 kD heat shock protein. Results: Seven Lutzomyia species were identified: Lu. evansi, Lu. gomezi, Lu. panamensis, Lu. dubitans, Lu. cayennensis cayennensis, Lu. rangeliana and Lu. trinidadensis. The first three species have epidemiological importance in Colombia because of their implications in the transmission of the Leishmania parasite. Sixty-five tissue samples from 19 D. marsupialis individuals were negative for Leishmania spp. Conclusions: The presence of the Lutzomyia species that have been identified as vectors for Leishmania inside and around houses in the village of El Bledo, in El Carmen de Bolívar represents a risk of infection. Furthermore, the presence of Lu. panamensis is reported for first time in El Carmen de Bolívar in Colombia. Although the lack of detection of Leishmania spp. in D. marsupialis samples may suggest that D. marsupialis does not play an important role in the transmission cycle of Leishmania in this region, it is necessary to carry out further longitudinal studies to confirm this hypothesis.